Evaluating Childhood Bipolar Disorder - A Survey of School Psychologists’ Knowledge and Practices - Mayo, Linda A.; Mayo, Joseph A. (Journal of the American Academy of Special Education Professionals, 2008)
Using data gathered from the "Childhood Bipolar Disorder Survey," this study explored Pennsylvania school psychologists’ knowledge and practices when evaluating children for Bipolar Disorder (BPD). Results indicate that only a small percentage of school referrals involved children or adolescents with BPD. Participating school psychologists were moderately familiar with both the literature and psychopharmacology surrounding childhood BPD. Although doctoral-prepared school psychologists were permitted to diagnose childhood BPD more than non-doctoral practitioners, approximately half of participants trained to diagnose childhood BPD were not allowed to do so in their respective schools. Participants identified disturbed mood, depression, grandiosity, rapid cycling, and sensation seeking as the more important symptoms influencing their understanding of childhood BPD. School psychologists used clinical history, formal diagnostic criteria, collateral data, and behavioral observations as their main instruments when making a diagnosis. Educational implications and future directions for research are discussed.